The New Shopping Center Site-selection in Urban Areas by Using AHP Model; Case Study: City of Saghez - Rasol Ghorbani; Nader Parvin; Jamal Gherisarian (نشریه جغرافیا و برنامه‌ریزی, 2013)
In the modern urban planning using GIS for land use analysis is usual and efficient. Distribution of shopping centers as one of urban land uses plays important role in urban planning and its rearrangement. It seems that using the AHP extensions for site-selection of new shopping centers can aid improve urban structures and increase urban efficiency. The main goal of this research is to survey and analyze suitable locations for constructing new shopping centers in Saghez. The city has located in Northwest of Kordestan province and its population is 131329 based on the report of Iranian Census Center in 1385. Majority of the residents do not have proper access to high quality shopping centers and therefore the current research aims to use AHP topropse new shopping centers locations in Saghez. The results of this research show that the distribution of shops and commercial centers in this city have not adapted with urban planning standards and construction of new shopping centers in districts 3 of Saghez city would provide optimal distribution of commercial centers, and improve accessibility and proper services for residences in city.